(untitled) (Research, Society and Development, 2020)
This work on playfulness in the teaching and learning process is justified by the relevance of the reflection on the use of playful methodologies in facing historical difficulties, related to the learning of mathematics. The objective of this article is to present a Case Study that involves the learning of the mathematical contents of high school students at the State’s High School of Matina-BA. In a qualitative and quantitative approach, the investigation established a comparison between traditional and playful methodologies and statistically analyzed the results of these strategies in the teaching-learning process, revealing the degree of ease or difficulty in each activity. To that end, the theoretical contribution from the perspective of Saviani was chosen as a possibility for critical-reflexive dialogue with other authors in the field. The results of the comparison using the paired t-test showed that there is an improvement in learning after playing games for teaching mathematics. In addition, it was noticed, through the Kruskal-Wallis test, that there is a difference between the rank of correct answers in relation to the classes, at the level of 10% of significance. This study revealed that the use of playful methodologies makes teaching mathematics more efficient and effective and learning more meaningful and enjoyable. However, in addition to playfulness, reflection on innovative educational practices is necessary, because in a class society it is essential to ensure that students appropriate the knowledge historically constructed in order to equip the working class for their social emancipation.